Impacts of kerosene contamination on the geotechnical characteristics of cohesive soil - O.Karkush, Mahdi; G.Jihad, Amer (International Journal of Engineering and Technology, 2019)
The soil contamination is a big problem which increased recently because of urbanization and development of industrial activities. The most common types of soil contaminants are petroleum products, fertilizers, heavy metals, pesticides, and organic compounds. This study focuses on the influence of kerosene on the chemical, physical, and engineering characteristics of cohesive soil. The soil samples are obtained from of a rural area in Al-Diwaniya city located in the south of Iraq. The soil samples are artificially contaminated with three ratios of kerosene (10, 30, and 50) % calculated based on the dry weight of soil. The process of contamination includes air dried the disturbed soil samples, then the soils samples placed in containers made from plastic and mixed with the field moisture content and the specified content of kerosene to ensure getting homogenous contaminated soil samples. The contaminated soil samples left for 30 days in plastic containers covered by nylon sheets to control the moisture content and the content of contaminant. A detailed testing program are conducted on these soil samples to determine the effects of kerosene on the chemical and geotechnical properties of silty clay soil sample. The results of tests proved that different percentages of kerosene have different influence on the chemical, physical, and mechanical properties of the tested soil samples.Â Â